Sosialisasi Penerapan SAK EMKM dan Strategi Marketing Mix dalam Peningkatan Profitabilitas untuk Mewujudkan Kemandirian Petani Nira Kelapa di Desa Plana Kecamatan Somagede - Sania Ferika; Laila Rossana; Riztina Dwi Setyasih (Universitas Kristen Indonesia Toraja, 2024)
Plana Village is located in Somagede District, Banyumas Regency, 25 Km or around 36 minutes from the Nahdlatul Ulama University Purwokerto campus, with an area of 340,646 Km2 and a population of 3,680 people. Based on village potential data in Banyumas Regency, Plana Village is one of the underdeveloped villages where the majority of the population makes their living as farmers. Brown sugar production is a community business in Plana Village that has the potential to be developed but has many obstacles, including financial record keeping which is still very simple, the resulting product packaging still uses banana leaves or makeshift plastic bags, does not yet have a brand and product label, limited marketing scope, channels long distribution and minimal price information resulting in low selling prices which then makes the business considered unprofitable. Based on several of these problems, the aim of the PKM Team is to socialize the implementation of SAK EMKM and marketing mix strategies to increase profitability to realize the independence of coconut sap farmers in Plana Village, Somagede District. The actions that will be taken are to provide socialization and assistance regarding the preparation of financial reports based on SAK EMKM and running a business using a marketing mix strategy, namely by (1) The quality of the products produced by coconut sap farmers must continue to be maintained, (2) Pay attention to prices, where these prices must be higher than production costs. However, prices must also be taken into account according to the quality of the product, (3) The marketing location must be easily accessible to consumers, both physical locations and using digital models, (4) Provide input regarding promotions carried out both physically and digitally.